Encadenamiento por inyección óptica de un láser DFB con la dispersión de brillouin - Castro Muñoz, M.; Spirin, V.V. (Revista Mexicana de Física, 2008)
We reported novel optical injection locking (OIL) configurations to generate a frequency and intensity stable Stokes signal without microwave generator and optic modulator. The first configuration based on OIL of DFB laser on Brillouin fiber ring laser radiation and second one on self-injection locking on Brillouin amplified radiation. Comparing the noise level of both configurations we found that second provides significantly more intensity and frequency stable Stokes signal. These configurations can advantageously be utilized in probe Stokes signal generation for distributed fiber optical Brillouin sensing.